The Influence of Intellectual Capital on Firm Value: The Mediating Role of Profitability - Kesuma, Satrio Fajar; Ratnawati, Kusuma (Jurnal Management Risiko dan Keuangan, 2025)
Purpose – This study aims to analyze the effect of intellectual capital on firm value, with profitability as a mediating variable, focusing on both direct and indirect relationships among the variables.     Design/methodology/approach –  This research employs a quantitative explanatory design. The analysis uses path analysis and the Sobel test to examine the hypotheses. The sample consists of 100 observations selected through purposive sampling based on specific criteria during the 2019–2023 period.   Findings – The results show that intellectual capital has a significant direct effect on firm value. However, intellectual capital does not have a significant effect on profitability, and profitability does not significantly affect firm value. Therefore, profitability does not mediate the relationship between intellectual capital and firm value.   Originality/value – This study provides evidence that intellectual capital influences firm value directly rather than through profitability, emphasizing the strategic role of intangible assets in corporate value creation.